Book Review of Self-studies in Rural Teacher Education by A. Schulte & B. Walker-Gibbs - Casie Thomas Jakubowski (Journal of Research in Rural Education, 2016)
Self-studies in Rural Teacher Education provides audiences with an engaging, international perspective into the use of self-study in research and practice in rural settings. Researchers will fi nd the volume useful in its description of the current state of self-studies in educational practice; the citations in each chapter offer a wealth of resources. Teacher educators will fi nd the book useful for the case studies of teaching in rural settings; the descriptions provide discussion points for classes engaged in teacher education. The book emerged from a desire by the two editors to expand the body of research in rural teacher education, and the chapter authors are knowledgeable in both rural research and self-studies. It connects well with White and Corbett's (2014) edited volume, Doing Educational Research in Ru ral Settings, introducing researchers to rural settings in which the authors present their paths to doing educational research in rural places. There are parallel themes between the two texts, as authors in each work have a deep commitment to research in rural environments and the students that these rural schools serve.